Immediate Effects of Yoked Prism on Gait in Individuals with Acquired Brain Injury. - Durham, Susan; Bedel, Nathan; Privette, Alma; Vallabhajosula, Srikant (Optometry & Visual Performance, 2025)
Background: Common symptoms associated with acquired brain injuries are due in part to poor integration of the sensorimotor system, thereby altering the visual midline, a deficit described as Visual Midline Shift Syndrome (VMSS). Yoked prism lenses have the potential to alter visual midline to improve visuo-spatial processing and gait. The purpose of this study was to determine the immediate effects of yoked prisms on gait and gait variability in individuals with acquired brain injuries. Methods: Twenty-four individuals with acquired brain injuries completed two to four trials of barefoot walking across an instrumented walkway under two conditions with current refractive compensation: without yoked prisms and with yoked prism lenses. Gait speed, stride length, stride width, single support percentage, and plantar pressure were extracted and averaged across the trials within each condition. Plantar pressure was divided into forefoot, midfoot, hindfoot, medial, and lateral regions. A paired samples t-test was used to compare the spatiotemporal gait parameters between both conditions, and a 3-way ANOVA was used to compare plantar pressure among the regions bilaterally for both of the conditions. Results: Wearing yoked prism lenses, participants walked with a significantly greater gait speed (by 6.8%; p < 0.001), stride length (by 4.9%; p = 0.002), single support phase (by 1.5%; p = 0.034), and cadence (by 2.6%; p = 0.002). Participants also showed lesser stance time variability (by 33.5%; p = 0.025) while walking wearing yoked prism lenses. Stride width and shifts in plantar pressure showed no significant changes (p > 0.05). Conclusion: Participants with acquired brain injuries who wore yoked prism lenses may experience improvements in sensorimotor system integration, which can result in the remediation of VMSS and immediate improvement of gait. Optometrists should consider using yoked prisms to treat VMSS. Long-term effects need to be further examined.